Interventions to increase young people's interest in STEM. A scoping review - Sáinz, Milagros; Fàbregues, Sergi; Romano, María José; López, Beatriz-Soledad (Frontiers in Psychology, 2022)
The underrepresentation of young people and particularly young women in many STEM fields has inspired various intervention programmes and research intended to boost their interest in these areas. The purpose of this scoping review is to examine the characteristics and effectiveness of interventions designed to encourage interest in STEM among secondary school students, particularly female students, over the past 20 years. A systematic search of the literature in five databases and additional search strategies resulted in identifying 215 studies evaluating interventions in different disciplinary fields. Data extraction and synthesis of these studies were carried out, focusing on the methodologies and theoretical foundations used. Twenty-five exemplars were selected to illustrate best practices in designing and evaluating interventions that address the various facets of young people’s lack of interest in STEM. These interventions attempt to modify and/or manipulate multiple environmental and school factors to impact students’ personal factors associated with STEM interest, such as achievement, self-perception of ability, and self-efficacy. Implications for the design of future interventions and potential outcomes are then discussed.